Association Between Upper Respiratory Tract Viral Load, Comorbidities, Disease Severity, and Outcome of Patients With SARS-CoV-2 Infection. (3rd January 2021) - Maltezou, Helena C; Raftopoulos, Vasilios; Vorou, Rengina; Papadima, Kalliopi; Mellou, Kassiani; Spanakis, Nikolaos; Kossyvakis, Athanasios; Gioula, Georgia; Exindari, Maria; Froukala, Elisavet; Martinez-Gonzalez, Beatriz; Panayiotakopoulos, Georgios; et al.
Abstract: Background: There is limited information on the association between upper respiratory tract (URT) viral loads, host factors, and disease severity in SARS-CoV-2–infected patients. Methods: We studied 1122 patients (mean age, 46 years) diagnosed by polymerase chain reaction (PCR). URT viral load, measured by PCR cycle threshold, was categorized as high, moderate, or low. Results: There were 336 (29.9%) patients with comorbidities; 309 patients (27.5%) had high, 316 (28.2%) moderate, and 497 (44.3%) low viral load. In univariate analyses, compared to patients with moderate or low viral load, patients with high viral load were older, more often had comorbidities, developed Symptomatic disease (COVID-19), were intubated, and died. Patients with high viral load had longer stay in intensive care unit and longer intubation compared to patients with low viral load ( P values < .05 for all comparisons). Patients with chronic cardiovascular disease, hypertension, chronic pulmonary disease, immunosuppression, obesity, and chronic neurological disease more often had high viral load ( P value < .05 for all comparisons). In multivariate analysis high viral load was associated with COVID-19. Level of viral load was not associated with any other outcome. Conclusions: URT viral load could be used to identify patients at higher risk for morbidity or severe outcome. Abstract : Patients with comorbidities more often had high upper respiratory tract viral load. Patients with high viral load more often developed COVID-19, were intubated, or died. Viral load could be used to identify high risk for morbidity or severe outcome.